Synthesis and Characterization of Nanoparticle Composite CaO/Fe3O4 from Duck Egg Shells and Its Application for Congo Red and Procion Red MX-5b Dyes Adsorption - Widia Purwaningrum; Fahma Riyanti; Julinar Julinar; Poedji Loekitowati Hariani; Bijak Riyandi Ahadito; Siti Chodijah; Vika Putri Safira (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
In order to improve the adsorption performance of CaO prepared from duck egg shells, a 1:1 composite of CaO/Fe3O4 were synthesized using a coprecipitation method. This composite was then used to adsorb Congo red and Procion red MX-5b dyes from an aqueous solution. The adsorption process was studied by investigating the effects of contact time, temperature, and initial concentration of dye. It was found that the optimum conditions for Congo red adsorption are 50 minutes of contact, 50 Â°C, and 225 mg/L of dye, while for Procion red MX-5b the conditions are 50 minutes of contact, 60 Â°C, and 250 mg/L of dye. The behavior of both adsorbents at equilibria follows a pseudo-second-order kinetic model and Langmuir isotherm, with the adsorption capacity at optimum condition for Congo red and Procion red MX-5b 46.95 mg/g and 47.39 mg/g, respectively. Thermodynamics studies showed that the adsorption process of Congo red was endothermic, while Procion red MX-5b was exothermic, yet both were found to happen spontaneously.